Active control of suddenly expanded flow - Khan, Sher Afghan; Sellappan, Rathakrishnan (2000)
This paper presents the results of an experimental investigation carried out to control the base pressure in a suddenly expanded axi-symmetric passage. An active control in the form of microjets was employed to control the base pressure. Microjets at four locations in a pitch circle diameter at the base was used as the active control. The jet Mach numbers at the entry to the sudden expansion was varied from 1.25 to 3.0. The area ratio of the present study is 3.24. The enlarged duct length-to-diameter ratio was varied from 10 to 1. The nozzle generating the above jet Mach numbers were operated with nozzle pressure ratio (NPR) in the range from 3 to 11. The wall pressure distribution in the enlarged duct was also measured to account for the effect of the active control on the enlarged duct pressure field. It is found that the microjets act as an effective control for controlling the base pressure field. A maximum of 35 percent increase in base pressure was achieved for certain combination of parameters.